Garrison Institute on Aging—Lubbock Retired and Senior Volunteer Program (RSVP) Provides Services to South Plains, Texas - Blackmon, Joan; Boles, Annette N.; Reddy, P. Hemachandra (Frontiers in Aging Neuroscience, 2015)
The Texas Tech University Health Sciences (TTUHSC) Garrison Institute on Aging (GIA) was established to promote healthy aging through cutting edge research on Alzheimer ’s disease (AD) and other diseases of aging, through innovative educational and community outreach opportunities for students, clinicians, researchers, health care providers, and the public. The GIA sponsors the Lubbock Retired and Senior Volunteer Program (RSVP). According to RSVP Operates Handbook, RSVP is one of the largest volunteer efforts in the nation. Through this program, volunteer skills and talents can be matched to assist with community needs. It is a federally funded program under the guidance of the Corporation for National and Community Service (CNCS) and Senior Corps (SC). Volunteers that participate in RSVP provide service in the following areas: food security, environmental awareness building and education, community need-based volunteer programs, and veteran services.